Realizing Africa's rice promise [ - Wopereis, M. (CABI, 2013)
At a time when Africa's food security stands threatened, ""Realizing Africa's Rice Promise"" provides a comprehensive overview of state-of-the-art research and recommendations for dealing with future challenges. With contributions from the key scientits working on rice in Africa, this volume addresses policy, genetic diversity and improvement, sustainable productivity enhancement, innovations and value chains. The book is useful for researchers, policy makers, agricultural ministries, donors, regional and sub-regional organizations, non-governmental development organizations and universities